Role of inflammasome genetics in susceptibility to HPV infection and cervical cancer development. Issue 9 (20th April 2016) - Pontillo, A.; Bricher, P.; Leal, V.N.C.; Lima, S.; Souza, P.R.E.; Crovella, S.
Abstract : Problem: Only a small proportion of HPV+ women develop virus‐associated lesions and cervical cancer, suggesting that other factors are involved in HPV+ keratinocyte transformation. Immune response plays an important role in clearing HPV infection, and host genetic variants resulting in defective immune response have been associated with virus persistence and/or cervical cancer. Considering that genetic variations in inflammasome genes were previously associated with viral infection and cancer development, the present study investigates selected single nucleotide polymorphisms (SNPs) in inflammasome genes as a possible risk factor for HPV infection susceptibility and/or for progression to cervical cancer. Patients and methods: 12 SNPs in seven inflammasome‐related genes ( NLRP1, NLRP3, NLRP6, CARD8, IL1B, IL18, TNFAIP3 ) were genotyped in a Brazilian HPV+ case/control cohort (n = 246/310). Multivariate analysis was performed in case/control as well as in HPV+ women stratified by the presence or severity of histologic lesion, HPV persistence, and type of virus. Results: IL1B rs1143643 was associated with protection against HPV infection in case/control analysis. NLRP1 rs11651270 plays a protection role against HPV persistence and/or oncogenesis. NLRP3 rs10754558 and IL18 rs1834481 exert a beneficial role against HPV persistence. NLRP3 rs10754558 variant resulted significantly associated with a lower risk to be infected with a high‐risk HPV. Conclusion: Our findings for the first time demonstrated that inflammasome genetics could affect HPV/host interaction in terms of virus susceptibility as well as of virus/persistence and cervical cancer progression. J. Med. Virol. 88:1646–1651, 2016 . © 2016 Wiley Periodicals, Inc.